Undersizing the Exeter stem in hip hemiarthroplasty increases the risk of periprosthetic fracture. Issue 4 (July 2020) - Korsnes, Lars; Gottvall, Andreas; Buttazzoni, Christian; Mints, Michael
Introduction: Whether under- or oversizing of the femoral component of cemented hip hemiarthroplasties impacts the risk of periprosthetic fractures (PPF) has only been examined experimentally. This study was carried out to add more knowledge about the risks of PPF in cemented polished tapered hemiarthroplasties. Methods: 20 patients with PPF following hip hemiarthroplasty with cemented Exeter V40 stems were compared to 50 controls who never suffered PPF having received the same type of Exeter hemiprosthesis for the same indication. The difference between stem size and post-hoc radiographic ideal templated size was investigated as a predictor of PPF. Results: Cases had a median size difference to post-hoc templating of –2, while controls had a median size difference of –1 ( p = 0.09). An ROC curve constructed to find an optimal cutoff point in size difference between cases and controls arrived at an area under curve of 63%, with –1.5 as the cutoff. Patients with size differences exceeding –1.5 had a statistically significant increased PPF risk (odds ratio = 3.8, 95% confidence interval, 1.1–13.3, p < 0.05). This group covered 55% of all cases. Conclusion: An implanted femoral component that is 2 or more sizes smaller than the template that is shown to be appropriate will increase the risk of PPF in Exeter hip hemiarthroplasties.